2022
DOI: 10.1186/s12913-022-08988-y
|View full text |Cite
|
Sign up to set email alerts
|

Does fragmented cancer care affect survival? Analysis of gastric cancer patients using national insurance claim data

Abstract: Background We aimed to investigate the association between fragmented cancer care in the early phase after cancer diagnosis and patient outcomes using national insurance claim data. Methods From a nationwide sampled cohort database, we identified National Health Insurance beneficiaries diagnosed with gastric cancer (ICD-10: C16) in South Korea during 2005–2013. We analyzed the results of a multiple logistic regression analysis using the generalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Given that previous studies indicate that primary care physicians play a vital role in cancer CC by managing comorbid conditions [ 23 ], the pandemic is likely to have further exacerbated the high-turnover and challenges with finding general medical providers felt by the participants. Furthermore, other studies have also shown that fragmented cancer care results in longer time to treatment and increased mortality while potentiating existing socioeconomic disparities [ 24 , 25 ]. Some of the participants were worried about these delays because they feared further cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Given that previous studies indicate that primary care physicians play a vital role in cancer CC by managing comorbid conditions [ 23 ], the pandemic is likely to have further exacerbated the high-turnover and challenges with finding general medical providers felt by the participants. Furthermore, other studies have also shown that fragmented cancer care results in longer time to treatment and increased mortality while potentiating existing socioeconomic disparities [ 24 , 25 ]. Some of the participants were worried about these delays because they feared further cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…In South Korea, recent studies have found that FC was associated with higher mortality among patients with various cancers [13][14][15]. Moreover, efforts to decrease FC and integrate complex cancer care within appropriate healthcare delivery systems may improve survivorship among patients with cancer [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In South Korea, recent studies have found that FC was associated with higher mortality among patients with various cancers [13][14][15]. Moreover, efforts to decrease FC and integrate complex cancer care within appropriate healthcare delivery systems may improve survivorship among patients with cancer [13,14]. In South Korea, there is no strict gatekeeping system for controlling healthcare utilization, and it is relatively easy for patients to access primary and secondary care and services in tertiary hospitals [16].…”
Section: Introductionmentioning
confidence: 99%